Development of E-Module Based On Ethnomathematics to Improve Problem Solving Skills on Integer Material for Class VI Elementary School Students - Ratna Puspasari, Tri; Fitrotun Nisa, Ana (International Conference on Elementary Education, 2025)
This research aims to develop an ethnomathematics-based E-Module as a solution to enhance students’ problem-solving abilities, particularly in integers for sixth-grade students. The study employs a Research and Development (R&D) approach using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. This method integrates local cultural elements to strengthen the relevance and understanding of mathematical concepts among students. The research findings indicate that the ethnomathematics-based E-Module effectively improves students’ problem-solving skills. During the pretest stage, the average student score was 70.30 with a proficiency rate of 40.75%, which increased to 85 with a proficiency rate of 86.88% in the posttest after using the E-Module. Expert evaluations also confirm the module’s high suitability for educational contexts, with validation scores ranging from 85-95%. Furthermore, the E-Module not only facilitates students’ understanding of integer concepts but also enhances their problem-solving skills through culturally relevant approaches. The implications of this research suggest further development in mathematics education by leveraging technology to enhance student engagement and understanding.